CURRENCY DEPRECIATION AND CAPITAL MARKET PERFORMANCE IN NIGERIA - Joel, Ihenyen Confidence; Wisdom, Epekele; Diweri, Owonaro Dorcas (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
This study looks at the effects of the weakening currency on Nigeria's stock market. Secondary data from the Nigerian Stock Exchange and the Central Bank of Nigeria is analyzed using a quantitative research methodology. Purposeful sampling and multiple regression analysis are used to examine the link between currency depreciation and stock market performance in this investigation. Depreciation of a currency was found to correlate negatively with the performance of capital markets even after controlling for other variables in the model. The results suggest that investors and regulators should keep in mind the potential negative effects of currency depreciation on the efficiency of capital markets.